Radioimmunotherapy for high-grade glioma. (June 2013) - De Bonis, Pasquale; Lofrese, Giorgio; Anile, Carmelo; Pompucci, Angelo; Vigo, Vera; Mangiola, Annunziato
Patients with high-grade glioma (HGG) still have a very poor prognosis. The infiltrative nature of the tumor and the inter- and intra-tumoral cellular and genetic heterogeneity, leading to the acquisition of new mutations over time, represent the main causes of treatment failure. Radioimmunotherapy represents an emerging approach for the treatment of HGG. Radioimmunotherapy utilizes a molecular vehicle (monoclonal antibodies) to deliver a radionuclide (the drug) to a selected cell population target. This review will provide an overview of preclinical and clinical studies to date and assess the effectiveness of radioimmunotherapy, focusing on possible future therapies for the treatment of HGG.